Expanding the Applicability of Sampson and Laub’s Theory of Inequality and Social Control: A Multilevel Examination: - Peck, Jennifer H. (Criminal justice and behavior, 2019)
The present study uses Sampson and Laub’s theory of inequality and social control to examine whether underclass poverty and racial/ethnic inequality hold current relevancy over the court processing of juvenile offenders. Hierarchical generalized linear modeling was used to investigate the impact of community aspects, offender characteristics, and offense-related factors on juvenile court outcomes occurring at intake, adjudication, and judicial disposition. Findings indicate limited evidence for the anticipated relationships between underclass poverty and racial/ethnic inequality on court processing stages. The individual and combined impact of being Black or Hispanic, and/or charged with a drug offense, exerted stronger effects on juvenile justice decision-making compared with Sampson and Laub’s structural factors. Implications for addressing the federal Disproportionate Minority Contact (DMC) Mandate based on the findings are discussed, as well as the future empirical inquiry surrounding whether community factors interact with offender and offense characteristics to influence outcomes of youth referred to juvenile court.